The Role of Vitamin E in Enhancing the Efficacy of Tamoxifen on Sperm Parameters in Male Infertility: A Clinical Experimental Study: Vitamin E and Tamoxifen in Male Infertility Treatment - Tazion, Shazia; Fauzia Butt; Sundas Zafar; Zahida Zakir; Hadia Zulfiqar; Anees Fatima (Journal of University College of Medicine and Dentistry, 2025)
Objective: To compare the outcome of tamoxifen versus tamoxifen plus vitamin E on the semen quality of infertile males with abnormal semen parameters. Methods: This clinical experimental study was done in the Department of Obstetrics and Gynecology, Sharif Medical City, Lahore for 6 months after approval from the hospital's ethical review board from January 15, 2024 till July 15, 2024. A total of 110 infertile males provided written consent and underwent semen analysis. Infertile married males aged 20 to 40 years and diagnosed with abnormal semen parameters were included in this study. Patients having leukocytospermia, diminished testicular volume, severe oligospermia were excluded from the study. Demographics and baseline data were recorded and participants were divided into group A which received oral Tamoxifen 10mg twice daily for three months, while Group B received Tamoxifen 10mg plus capsule vitamin E 400mg once a day orally. After three months, semen analysis was repeated to assess changes in sperm parameters. Data collection adhered to a pre-designed proforma. Results: The mean age in both the groups was 29.40+3.89 years; sperm count in Group A increased from 6.13+0.92 to 16.31+1.33 and in Group B 6.16+0.90 to 19.83+1.58 (p=0.000), and motility increased from 13.98+1.00 to 30.58+2.13 in Group A and 14.05+1.04 to 34.69+1.90 in Group B, (p=0.001) Conclusion: Our study findings strongly support the synergistic effect of combining tamoxifen with vitamin E in enhancing sperm motility, providing valuable insights for potential therapeutic interventions in male infertility.